Education : - Spencer, Herbert (Watts & CO., 1903)
The growing demand for the original edition of these chapters on Education has suggested to me the propriety of issuing an edition that shall come within easy reach of a larger public: what knowledge is of most worth, intellectual education, moral education, physical education.